Record of the genera Versuriga and Cassiopea (Scyphozoa) in the coastal waters of Vietnam - Ha, Tran Manh; Thu, Pham The; Nishikawa, Jun (Vietnam Journal of Marine Science and Technology, 2020)
Scyphozoans are currently causing great concern because of their blooms in the marine environment. During the field surveys in Cat Ba and Hon Me islands in 2019 and Thuy Trieu lagoon in June 2020, we found rhizostome jellyfish that had rarely recorded in Vietnamese waters. These specimens had the following morphological characters: Hemispherical umbrella with reticular grooves; eight large semicircular velar lappets alternating with narrow lappets in each octant; laterally flattened mouth-arms with numerous flat, membranous branches bearing many clubs and intermediate filaments; non-anastomosed broad perradial canals and anastomosed narrow interradial canals. The morphological characters of these rhizostome jellyfish were consistent with descriptions of Versuriga anadyomene. In addition, the morphology of some of other jellyfish bloomed in a marine lake was consistent with those of Cassiopea andromeda with a broad, shallow, aboral concavity; about 19 rhopalia; 4 square lappets per paramere; oral arms round in cross section, about 1.5 times as long as bell radius; 4–6 alternate branches, bifurcated distally; 1–2 appendages stemming from the central point of the disk, plus one at the base of each pair of oral arms, plus one at distal bifurcation of each oral arm or lacking; coloration yellow-brown with white or pale spots and streaks, size of the letter different with others (bigger), ocelli not observed. This paper reported the occurrence of rare scyphozoans, Versurigia anadyomene and Cassiopea andromeda in Vietnamese waters.